GROWTH PATTERN ANALYSIS OF SPRING SOWN CAMELINA [CAMELINA SATIVA L. (CRANTZ.)] DUE TO VARIATION OF SOWING TIME - M. Göre; O. Kurt; H. Uysal (Journal of Animal and Plant Sciences, 2022)
This research was conducted to determine the change of main growth parameters and growth pattern of camelina depending on the sowing time and genotype. The research was carried out during 2017 and 2018 and the treatments (1, 11, 21 and 31 May & PI-650142 and PI-304269 genotypes) were arranged in split-plot design and 3 replications. It was determined that NAR, LAI, RGR and DM were affected by the sowing times. In addition, NAR, LAI and RGR were significantly affected by genotypes at all growth stages, whereas DM was affected only in the pre-flowering stage. Depending on the sowing times and genotype, NAR was found 0.014-0.016, 1.65-1.96 and 4.10-15.51 mg mm-2 day-1 in pre-flowering, flowering and post-flowering periods, respectively, while LAI was found 0.22-0.29, 0.23-0.33 and 0.10-0.23 mm2 mm-2, respectively. In pre-flowering, flowering, post-flowering and harvest period RGR was found 2.3-2.6, 3.3-4.4, 2.2-3.3 and 0.6-0.7 mg g-1 day-1 g-1 day-1, respectively, while DM was 0.233-0.283, 0.410-0.553, 0.646- 0.944 and 0.939-1.003 g per plant, respectively. Also, depending on the sowing time, the seed yield was determined as 190.85-810.07 kg ha-1 for the PI-650142 genotype and 190.94-360.65 kg ha-1 for the PI-304269 genotype. Consequently, it can be suggested that PI-650142 genotype can be used for general sowing once date is adjusted to 1 May in conditions of Samsun. This could be contributed to optimum temperature and day length during the flowering, seed formation and filling stage.
Keywords: camelina; sowing time; growth pattern; NAR; LAI; RGR; DM; Seed yield